Pattern-Reconfigurable Yagi-Uda Antenna Based on Liquid Metal - Hao, Jiaxiang; Ren, Jian; Du, Xiaoyu; Mikkelsen, Jan Hvolgaard; Shen, Ming; Yin, Ying Zeng (IEEE antennas and wireless propagation letters, 2021)
A pattern-reconfigurable Yagi-Uda antenna based on liquid metal is presented. The antenna consists of a balun-fed active dipole and a pair of stretchable passive parasitic dipoles, which are implemented by eutectic gallium-indium (EGaIn) alloy embedded in microfluidic channels. The parasitic dipoles are driven at each end by two low-cost, three-dimensional printed media rods. Afterward, spinning the rods at different angles leads to varying degrees of stretching upon the stretchable dipoles. Note the length of passive parasitic dipoles is a vital factor for antenna radiation reconfiguration. The antenna exhibits bidirectional radiation if the parasitic dipoles are equal in length. Otherwise, directional radiation toward the shorter parasitic dipole direction can be obtained. Based on the above-mentioned working principle, a pattern-reconfigurable antenna working in wireless local area network (WLAN) band is fabricated and measured. Apart from the reconfigurable capability, the proposed antenna keeps operating in the WLAN band of 2.4-2.48 GHz during the whole shape deformation.